The The Essential Role of Human Nature in Shaping a Value-Based Islamic Educational Paradigm - Abdullah, Aji; Asy’arie, Musa; Shobahiya, Mahasri (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This article aims to conduct an in-depth examination of the role of understanding human nature in constructing a value-based paradigm of Islamic education. The background of this study is grounded in the observed weakness of the spiritual and ethical dimensions within modern education systems, which tend to be pragmatic and cognitively centered, as well as the lack of integration of transcendental values in contemporary Islamic educational practices. The research adopts a qualitative approach using normative-philosophical methods and library research techniques. Data are critically analyzed through a textual study of classical and contemporary works in Islamic educational philosophy, Islamic anthropology, and relevant educational documents. The findings reveal that understanding human nature as a being composed of physical, intellectual, emotional, and spiritual dimensions has direct implications for the design of Islamic educational systems. Islamic education must be holistically structured through three foundational pillars: an ontological understanding of the human being, education as a process of value internalization, and the integration of spiritual and social values into the curriculum and instructional practices. The practical implications include the development of a tawhid-based curriculum, reflective and participatory learning strategies, the teacher’s role as murabbi (nurturer) and muaddib (ethical guide), an evaluation system that assesses character and spirituality, and a learning environment that functions as a value-based ecosystem. The article concludes that an Islamic education grounded in the understanding of human nature not only offers a solution to the value crisis in modern education but also serves as a strategic framework for nurturing a generation of insan kamil individuals who are intellectually excellent, spiritually mature, and socially responsible. This study contributes both theoretically and practically to the development of a more humanistic and transformative Islamic education system.